2023
DOI: 10.1038/s41598-023-32078-6
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-resolved virus-host interactions in a municipal landfill include non-specific viruses, hyper-targeted viral populations, and interviral conflicts

Abstract: Viruses are the most abundant microbial guild on the planet, impacting microbial community structure and ecosystem services. Viruses are specifically understudied in engineered environments, including examinations of their host interactions. We examined host-virus interactions via host CRISPR spacer to viral protospacer mapping in a municipal landfill across two years. Viruses comprised ~ 4% of both the unassembled reads and assembled basepairs. A total of 458 unique virus-host connections captured hyper-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 77 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…This study makes use of 27 metagenomes that were sequenced from samples from three distinct landfills. Fourteen metagenomes were sequenced from an active municipal landfill and adjacent aquifer in Southern Ontario (SO), sampled twice one year apart (July 2016 [SO 2016] and October 2017 [SO 2017]) and described previously [9,35]. Nine metagenomes were from a northeastern United States active municipal landfill (NEUS) in which nine distinct cells, units in which waste is held within the landfill, were sampled in February 2019 as described previously [36].…”
Section: Sampling Sites and Metagenomesmentioning
confidence: 99%
See 3 more Smart Citations
“…This study makes use of 27 metagenomes that were sequenced from samples from three distinct landfills. Fourteen metagenomes were sequenced from an active municipal landfill and adjacent aquifer in Southern Ontario (SO), sampled twice one year apart (July 2016 [SO 2016] and October 2017 [SO 2017]) and described previously [9,35]. Nine metagenomes were from a northeastern United States active municipal landfill (NEUS) in which nine distinct cells, units in which waste is held within the landfill, were sampled in February 2019 as described previously [36].…”
Section: Sampling Sites and Metagenomesmentioning
confidence: 99%
“…Bacteriophages are predicted to be quite host specific, but recent studies have suggested the presence of phages with diverse host ranges in different environments. In research on both isolated phages [8] and those identified in silico, bacteriophages have been shown or predicted to infect across distinct bacterial phyla [1,[9][10][11] and domains of life [2,8,11]. While the mechanisms of viral infection across organisms from different phyla or domains are likely very complex and difficult to resolve without wet-lab experiments, the potential presence of such viruses with large host ranges and their isolation can be important for biotechnological applications including phage therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, predicting strain-specific interactions remains a difficult task, particularly because taxonomic markers are known to be a poor proxy for infection profiles [ (Sullivan NJ, 2003), (Kauffman KM, 2022)]. Recent studies have shown some improvement in resolving strain-specific interaction phenotypes, e.g., by using CRISPR spacers and metagenomic data to identify recent phage infection [ (Simon Roux, 2021), (Szabo RE., 2022), (George, 2023)] or by co-clustering phage and bacteria mutations, respectively, amongst strains that tend to interact as a means to identify associated gene or sequence differences [ (Kauffman KM, 2022)].…”
Section: Introductionmentioning
confidence: 99%